The use of the prone position in the preterm newborn and infant submitted to mechanical ventilation in cases of acute viral bronchiolitis (Research, Society and Development, 2021)
Introduction: Acute viral bronchiolitis is a respiratory disease that causes obstruction of the lower airways, leading to respiratory distress, more frequent in neonates, infants and children up to three years of age, with predominance in the first six months of life. Its main etiological agent is the respiratory syncytial virus present in 75% of hospitalization cases. Objective: To analyze the effectiveness of using mechanical ventilation associated with the prone position in infants with acute viral bronchiolitis. Methodology: It is a narrative review of literature, with research of scientific articles in online databases, published between 2015 and 2020, in Portuguese, Spanish, English, Italian and French. Results: 1,215 articles were found, they were analyzed through an adaptation of the Strobe table, of which, 7 were included in the discussion. Conclusion: It was possible to verify the effectiveness of the prone position associated with mechanical ventilation in lactating women and with acute viral bronchiolitis, improving both respiratory and cardiac efficacy, decreasing the time of ventilatory support in the infant.